2021
DOI: 10.1029/2020wr027346
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Integration Using Resistivity and Lithology for Improving Estimation of Hydraulic Conductivity

Abstract: The characterization of spatially heterogeneous hydraulic conductivity (K) is important in groundwater resources management. We propose a Bayesian statistical method that integrates multiple secondary data (continuous and category data) with primary data (K) to improve regional K field characterization. Considering the disparity of the data scale, spatial scarcity of primary and secondary data, and need for regional-scale site characterization, the aquifer thickness is used as the scale for data integration. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Boadu (2000) concluded the measurement of hydraulic conductivity by the laboratory and field methods as costly and time consuming, and insufficient field data of aquifers and hydraulic boundaries add to the limitation (Freeze & Cherry 1979;Todd & Mays 2005). These limitations have led researchers to shift to analytical approaches for the study of groundwater and the porous media (Salmasi & Azamathulla 2013;Cheng & Hsu 2021). Hazen (1893), Carman (1939), Sherard et al (1984), Vukovic & Soro (1992), Indraratna et al (1996) and Ishaku et al (2011) conducted investigations to suggest empirical equations for the hydraulic conductivity determination based on particle sizes of granular soils.…”
Section: Introductionmentioning
confidence: 99%
“…Boadu (2000) concluded the measurement of hydraulic conductivity by the laboratory and field methods as costly and time consuming, and insufficient field data of aquifers and hydraulic boundaries add to the limitation (Freeze & Cherry 1979;Todd & Mays 2005). These limitations have led researchers to shift to analytical approaches for the study of groundwater and the porous media (Salmasi & Azamathulla 2013;Cheng & Hsu 2021). Hazen (1893), Carman (1939), Sherard et al (1984), Vukovic & Soro (1992), Indraratna et al (1996) and Ishaku et al (2011) conducted investigations to suggest empirical equations for the hydraulic conductivity determination based on particle sizes of granular soils.…”
Section: Introductionmentioning
confidence: 99%
“…Verdet et al (2020) carried out true 3D ERT measurements on a karstic site and revealed the undercover karst features by combining 3D ERT with geomorphological and geological data. Cheng and Hsu (2021) fused resistivity logs and lithology description through Bayesian integration to improve the estimation of hydraulic conductivity for large-scale aquifer.…”
mentioning
confidence: 99%